ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERENCANAAN STRATEJIK DI SDN RANCAEKEK 05 KABUPATEN BANDUNG - Komara, Endang; Siti Muthia, Derifa; Agustendra, Apen; Lestari, Rahayu Dwi (STKIP Pesisir Selatan, 2025)
This article examines the learning design of Islamic Religious Education (PAI) based on democratic and multicultural values, which can be the answer to the identity crisis experienced by the younger generation in the modern era. In the midst of the influence of globalization, technological development, and increasingly complex cultural and religious diversity, religious education is required to be more than just conveying doctrine. This approach offers learning experiences that encourage active participation, open dialogue, and reflection on students' social reality. Using a qualitative approach, this research was conducted through literature studies and case studies in schools that apply democratic values in Islamic education learning. The results show that this learning model is able to create an inclusive classroom atmosphere, strengthen a sense of empathy, and shape the character of students who are open to differences. The role of the teacher also becomes very important, namely as a value companion and dialogue facilitator, not just a text teacher. Although promising, the implementation of this approach still faces obstacles such as limited teacher understanding, lack of policy support, and lack of contextualized teaching materials. Therefore, cross-stakeholder cooperation is needed to ensure that religious learning is able to form a generation that is religious, tolerant, and ready to coexist in a diverse society.